2019
DOI: 10.2298/gensr1903151m
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of tuber yield using unbalanced data from potato variety trials

Abstract: Potatoes are grown in a wide region and in different environments unlike other crops, so it is known as one of the most spread world crops. In many agriculture areas around the world new genotypes are included in many multi-locational experiments at a large number of locations and years to determine the level and the stability of yields. However, there are a lot of problems with this traditional approach mostly due to the large number of genotypes that require consistent checking of every genotype at numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The results are in accordance with Mijic et al (2019) and Flis et al (2014), who also observed higher influence of environment during the evaluation of potato varieties across the locations. Relatively low contribution of genetic variance to the total variance was also reported earlier (Mijic et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…The results are in accordance with Mijic et al (2019) and Flis et al (2014), who also observed higher influence of environment during the evaluation of potato varieties across the locations. Relatively low contribution of genetic variance to the total variance was also reported earlier (Mijic et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, in recent years, the best linear unbiased predictors (BLUPs) derived from mixed linear models are increasingly being used for the genetic assessment of segregating breeding populations [5][6][7]. The BLUPs facilitate the comparison of breeding clones from different populations evaluated in distinct environments, as well as analyzing unbalanced datasets resulting from testing trials [8]. The BLUPs predict random effects that show a covariance structure.…”
Section: Introductionmentioning
confidence: 99%